Acceptability and adherence of a candidate microbicide gel among high-risk women in Africa and India - Greene, Elizabeth; Batona, Georges; Hallad, Jyoti; Johnson, Sethulakshmi; Neema, Stella; Tolley, Elizabeth E. (An International Journal for Research, Intervention and Care, 2010)
Vaginal microbicides currently under development are substances that may prevent the transmission of HIV. Qualitative, in-depth post-trial interview data from a Phase III clinical trial of 6% Cellulose Sulfate microbicide gel in two sites in Africa (Uganda and Benin) and two in India (Chennai and Bagalkot) were examined in order to better understand factors that influence microbicide acceptability and adherence in a clinical trial setting. Women found the gel relatively easy to use with partners with whom there were no expectations of fidelity, in situations where they had access to private space and at times when they were expecting to engage in sexual intercourse. Adherence to gel seemed significantly more difficult with primary partners due to decreased perceptions of risk, inconvenience or fear of partner disapproval. Findings suggest that women in a variety of settings may find a microbicide gel to be highly acceptable for its lubricant qualities and protective benefits but that adherence and consistent use may depend greatly on contextual and partner-related factors. These findings have important implications for future trial designs, predicting determinants of microbicide use and acceptability and marketing and educational efforts should a safe and efficacious microbicide be found.
Keywords: Microbicide; Acceptability; Africa; India; HIV prevention; Adherence